ANALISIS PASAR VIRTUAL EVENT DI TENGAH PANDEMI COVID-19 - M. Tanggap Sasmita (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
Since the end of 2019 the world has been hit by the Covid-19 pandemic which has led to changes in life including the world of tourism more specifically in the MICE sector and events. MICE and Event sectors adapt to these changes, one of them is by holding virtual events. Virtual events during the pandemic developed from webinars, conferences, to performances. A virtual event is something new and needs to be analyzed in-depth, in this study virtual events are analyzed from the perspective of the market. By using survey research methods, by distributing online questionnaires to 100 people, it was found that virtual events still have the opportunity to continue to be produced in the future with the high interest of the community to participate in virtual event activities even though there are various obstacles in their implementation such as duration that is too long, monotonous, and improper broadcast time